Three Phases of Aldous Leonard Huxley's Approach to Modernity and Modernization - Hilal Kaya (Nalans, 2018)
Traversing disciplinary boundaries between literary studies, cultural studies and sociology, this study claims to be distinctive because it explores Huxley’s writings in relation to the issues of modernity and modernization. The study aims to foreground Huxley’s changing engagement with modernity and modernization that informs his novels, Point Counter Point (1928) and Brave New World (1932). That is, when he wrote Point Counter Point his idea of the modern was closer to the liberal narrative of modernity: Point Counter Point idealizes “the West” and equates it with modernity. From Brave New World on, however, Huxley started to make a criticism of this understanding of the modern and re-conceptualized his attitude to modernity and modernization. He challenges the limits of conventional time and deconstructs the binaries between “the West” and “the East:” his novel, in other words, reconfigures modernity and modernization in ways that foreground multiple experiences and practices of modernity.